Exploratory analysis of medication adherence and social determinants of health among older adults with diabetes - M.L. Blakely; F. Sherbeny; T.J. Hastings; L. Boyd; O.A. Adeoye-Olatunde (Elsevier, 2023)
Background: Diabetes is the fifth leading cause of death in the United States (US), affecting approximately 27%, or 15.9 million adults 65 years of age and older. Diabetes is the most expensive chronic condition in the US and accounts for the second largest avoidable healthcare cost. Adherence to long-term medication treatment plans is crucial among patients with diabetes because it decreases risk of developing comorbid conditions and improves quality of life. Greater exposure to adverse social determinants of health (SDOH) over an individual's lifespan can result in worse health outcomes. Hence, it is important to obtain a better understanding of how social determinants of health (SDOH) influence patients' behaviors and affect medication adherence among older adults with diabetes. Objectives: Identify and prioritize SDOH associated with medication adherence among a nationally representative sample of older adults with diabetes. Secondary objectives were to characterize SDOH, estimate medication adherence, and explain implications for health disparity populations among older adults in the US who have been diagnosed with diabetes. Methods: This study used a cross-sectional secondary data analysis to examine the National Health and Nutrition Examination Survey database, identifying associations between SDOH and medication adherence among older adults with diabetes in the US. Results: A total of 1807 respondents' data were included in the analyses. Nearly three-quarters (73.9%) of patients were considered adherent to their oral diabetes medications. Multivariable analysis revealed significant differences in medication adherence based on disability status (p = 0.016), household balanced meals (p = 0.033), and interview language (p = 0.008). Conclusions: Results revealed those with a disability, those who could not afford a balanced meal, and/or those who spoke English were associated with a higher likelihood of being nonadherent to their diabetes medications in comparison to individuals not in these groups. These findings can assist in developing SDOH-centered medication adherence strategies for pharmacists to implement with older patients with diabetes.